Chronic granulomatous disease associated with Duchenne muscular dystrophy caused by Xp21.1 contiguous gene deletion syndrome: Case report and literature review - Bi, Shaohua; Dai, Liying; Jiang, Liangliang; Wang, Lili; Teng, Mia; Liu, Guanghui; Teng, Ru-Jeng (Frontiers in Genetics, 2023)
Chronic granulomatous disease (CGD) and Duchenne muscular dystrophy (DMD) are X-linked recessive disorders whose genes are 4.47 Mb apart within Xp21.1. A combination of both diseases is rare with only five cases reported in the literature where it is known as Xp21.1 “contiguous gene deletion syndrome”. We describe a male neonate who presented with sepsis at 19 days of age. The diagnosis of CGD with DMD was established through copy number variation sequencing (CNV-seq) with an extensive 7.5 Mb deletion of Xp21.2-Xp11.4 of the proband. One of his elder sisters and his mother are carriers. The deletion includes six known genes: glycerol kinase (GK), dystrophin (DMD), cilia- and flagella-associated protein 47 (CFAP47), gp91 (CYBB), Kell antigen (XK), and retinitis pigmentosa GTPase regulator (RPGR). Laboratory assays revealed an increased creatine kinase (CK) level, decreased gp91 expression, and a positive nitroblue tetrazolium test. Due to the extensive gene deletion and the poor prognosis, the family determined to pursue conservative management without further laboratory workup. The patient passed away from a fulminant infection at the age of three-month at a local medical facility. To the best of our knowledge, this case of Xp21.1 contiguous gene deletion syndrome represents the most extensive deletion of genes in this region ever reported. A literature review of similar cases is presented.